Differential cross section measurements for the production of a W boson in association with jets in proton–proton collisions at S=7 TeV - Karapınar, Güler; Karapınar, Güler (Elsevier, 2015)
Measurements are reported of differential cross sections for the production of a W boson, which decays into a muon and a neutrino, in association with jets, as a function of several variables, including the transverse momenta (pT) and pseudorapidities of the four leading jets, the scalar sum of jet transverse momenta (HT), and the difference in azimuthal angle between the directions of each jet and the muon. The data sample of pp collisions at a centre-of-mass energy of 7 TeV was collected with the CMS detector at the LHC and corresponds to an integrated luminosity of 5.0 fb−1. The measured cross sections are compared to predictions from Monte Carlo generators, MADGRAPH + PYTHIA and SHERPA, and to next-to-leading-order calculations from BLACKHAT + SHERPA. The differential cross sections are found to be in agreement with the predictions, apart from the pT distributions of the leading jets at high pT values, the distributions of the HT at high-HT and low jet multiplicity, and the distribution of the difference in azimuthal angle between the leading jet and the muon at low values. © 2014 The Authors
Keywords: CMS; Electroweak; Jets; Physics; Standard Model; Vector Boson; W + Jets